7SK small nuclear RNA, a multifunctional transcriptional regulatory RNA with gene-specific features. Issue 2 (15th March 2018) - Egloff, Sylvain; Studniarek, Cécilia; Kiss, Tamás
ABSTRACT: The 7SK small nuclear RNA is a multifunctional transcriptional regulatory RNA that controls the nuclear activity of the positive transcription elongation factor b (P-TEFb), specifically targets P-TEFb to the promoter regions of selected protein-coding genes and promotes transcription of RNA polymerase II-specific spliceosomal small nuclear RNA genes.